Mud and Frame Construction in South Leicestershire. - Finn, Neil (Vernacular Architecture, 2009)
There is evidence for the widespread use of unbaked earth as a building material in the East Midlands. In Leicestershire the construction of earth walling, or mud as it is generally referred to in this area, is documented from at least the fourteenth century. The documentary sources suggest that a greater variety of earth-building techniques once existed than is represented by surviving structures, which are mainly of monolithic mud construction. Fieldwork has identified one of these variant traditions for which the term 'mud and frame' has been coined. This is a coherent vernacular tradition with well-defined structural characteristics. It is likely to be one of a number of subtly different traditions in the region in which elements of earth and timber building techniques are combined. This paper outlines the structural characteristics of mud and frame buildings in south Leicestershire and draws some provisional conclusions regarding the origin, dating and status of this building type.